1998
DOI: 10.1017/s002196309700187x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Exposure to Violence in Urban Youth

Abstract: This study reports on the development of a structured interview, My Exposure to Violence (My ETV), that was designed to assess child and youth exposure to violence. Eighty participants between the ages of 9 and 24 were assessed. Data from My ETV were fit to a Rasch model for rating scales, a technique that generates interval level measures and allows the characterization of both chronic and acute exposure. Results indicated that the fit statistics for six scales, covering both lifetime and past year victimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
240
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 281 publications
(249 citation statements)
references
References 23 publications
3
240
2
Order By: Relevance
“…Wave 3 survey items assessing experience of violence were based on the Selner-O'Hagan et al assessment. 22 History of experiencing violence was measured by these seven items: "Have you ever been: (1) chased when you thought that you could really get hurt; (2) hit, slapped, punched, or beaten up; (3) attacked with a weapon; (4) shot; (5) shot at but not actually wounded; (6) sexually assaulted, molested, or raped; and (7) threatened to seriously hurt." Experiencing violence in the past year was based on an affirmative report of any of the seven types of violence.…”
Section: Methodsmentioning
confidence: 99%
“…Wave 3 survey items assessing experience of violence were based on the Selner-O'Hagan et al assessment. 22 History of experiencing violence was measured by these seven items: "Have you ever been: (1) chased when you thought that you could really get hurt; (2) hit, slapped, punched, or beaten up; (3) attacked with a weapon; (4) shot; (5) shot at but not actually wounded; (6) sexually assaulted, molested, or raped; and (7) threatened to seriously hurt." Experiencing violence in the past year was based on an affirmative report of any of the seven types of violence.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, lower SES has been associated with poorer psychological profiles (20). In healthy children, low SES has been associated with more frequent exposure to stressful life events (21)(22)(23), and children who live in low SES neighborhoods are more likely to report witnessing incidents of violence (24). Low SES also has been associated with greater threat interpretations during ambiguous life situations.…”
Section: Clinical Evidence For Ses Stress and Asthma Relationshipsmentioning
confidence: 99%
“…The five factors are (1) witnessed violence in the neighborhood, (2) victimized by violence or witnessed violence at home, (3) witnessed violence at school, (4) witness or victim of a shooting or knife attack, and (5) victimized by violence at school or in the neighborhood (Singer et al, 1995). Several studies have demonstrated the validity of using child and adolescent self-reports of exposure to violence (Martinez and Richters, 1993;Pastore et al, 1996;Selner-O'Hagan et al, 1998;Singer et al, 1995Singer et al, , 1999Song et al, 1998).…”
Section: Variables and Instrumentationmentioning
confidence: 99%